THU0413 Utility of The Spade Tool To Identify Axial Spondyloarthritis in Patients with Chronic Backpain. (15th July 2016) - Habibi, S.; Doshi, S.; Sengupta, R.
Abstract : Background: Many referral strategies have been devised to optimize the early diagnosis of axial spondyloarthritis (AxSpA). These result in the diagnosis of AxSpA in 30 to 40% of patients. Strategies to reduce the delay in diagnosis of AxSpA and optimise the appropriateness of referrals to secondary care should be explored. The Spondyloarthritis Diagnosis Evaluation (SPADE) tool (www.spadetool.co.uk has been designed to assist healthcare professionals define the probability of axial spondyloarthritis (AxSpA) in patients <45 years of age with chronic back pain and no definite changes on radiographs. The probability of AxSpA derived from the 'SPADE Tool' is displayed on a chart with clear instructions for the user on what action should be taken next. Objectives: To assess the performance of the SPADE tool in the secondary care setting. Methods: The RNHRD runs a weekly Early Back Pain (EBP) clinic. Data on all patients (AxSpA and Mechanical back pain) has been collected. The SPADE tool which consists of questions pertaining to clinical features, CRP, HLA-B27 and MRI findings was applied on all EBP patients utilizing data they were referred with (before Specialist advised investigations- MRI scan results) to obtain the probability of SpA as one of the 4 categories: Category 1-improbable, category 2-additional tests needed (HLA-B27 or MRI, consider referral to a specialist), category 3 (probable SpA) and category 4 (definitive SpA). A physicians diagnosis of AxSpA was used as the gold standard. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were estimated using observed ratios of patient numbers from this sample. 95% CIs on the NPV were generated by assuming a binomial model for x, where x is the number of patients with SpA who are not referred at a given SPADE threshold. Results: N=87 (49 males); 44 (50.5%) had SpA subsequently diagnosed; 6/27 in category 1, 26/44 in category 2, 5/7 in category 3 and 7/9 in category 4. Estimates of PPV, NPV, sensitivity and specificity obtained by using each of the SPADE categories as a threshold for referral are given in the table . Conclusions: The SPADE tool is a valuable resource to assist clinicians define the probability of SpA in patients with chronic back pain. The high NPV, especially with the referral threshold set at 2 or 3, implies that the test is most useful in ruling out SpA. Note that the prevalence of AxSpA in this sample is likely to be higher than in the target population (primary care), meaning that these estimates of NPV are likely to be underestimates. The tool needs to be validated in a primary care setting. Acknowledgement: The funding for the SPADE tool was provided through a Medical Education grant from Abviee Disclosure of Interest: None declared